Is there a parallax in the mind? Samuel Beckett and distance in the psychic archive. Issue 2 (1st February 2021) - Chattopadhyay, Arka
ABSTRACT: This paper examines the speculative presence of a parallax in the mind in the works of Samuel Beckett through the psychoanalytic lens of a Real parallax in the psychic archive. Navigating through Lacan, Žižek and Derrida, it establishes the parallax as a tool to ascertain psychic distance. The parallax sets out to measure the psychic topos that ultimately yield immeasurability as the essence of its vistas. The article goes through some important metaphorisations of the psyche as the inscribed space in Beckett's texts and finally zooms in on the late TV play … but the clouds … and his last extended prose text, Stirrings Still . Both these works historically warrant a parallax-reading as Beckett draws a parallax in one's stage directions and makes a cryptic inquiry about a psychic parallax, during the composition of the other. While the play uses the moving body as a cipher to chart the psychic space which establishes an insurmountable self-distance, a critical journey through the drafts of the prose-text exposes a complex notion of self-reference as a Real parallax of impossible distances.